Evaluation of 4DryField as an adhesion prophylaxis in pediatric patients: a propensity-score matched study - Klinke Petrowsky, Michaela; Dietze, Nina; Trautmann, Tina; Jank, Marietta; Martel, Richard; Elrod, Julia; Boettcher, Michael (European journal of pediatric surgery, 2024)
Introduction Abdominal adhesions following surgery can lead to complications like intestinal obstruction and pelvic pain. While no molecular therapies currently target the underlying adhesion formation process, various barrier agents exist. 4DryField® has shown promise in reducing bleeding and adhesions in adults. This study aimed to assess its effectiveness in children. Methods The study examined all pediatric patients who underwent laparotomy between January 2018 and February 2022. It compared outcomes between those treated with 4DryField® and a control group. Key endpoints included surgical revision, adhesion recurrence, infections, insufficiencies, fever, C-reactive protein (CRP) levels, and time to gastrointestinal passage. Results In total, 233 children had surgery for bowel adhesions. After propensity score matching, 82 patients were included in the analysis: 39 in the control and 43 in the 4DryField® group. 4DryField® did not affect the readhesion rate. Children in the treatment group had significantly more complications (47 vs. 15%, = 0.002), more often fever, and higher CRP levels. Conclusions 4DryField® did not show potential in reducing adhesion formation, but it was associated with significantly more complications in pediatric patients. Thus, future prospective studies are needed to evaluate the safety and effectiveness of 4DryField® in children.
Artikel online veröffentlicht: 28. Juni 2024
Gesehen am 26.11.2024